Crafting Joyful Writing Journey: Empowering Novice Authors With Strategies For Sustainable Expression - Rian Sigit Gesang Permana; Widya Rahmawati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This article describes how beginners can enjoy writing by practicing it in their daily lives. The researcher used library research into existing literature on writing practices. The main result of the article is a set of recommendations for beginners on how to make writing a fun and sustainable part of their everyday life. The article concludes by developing strategies that make writing enjoyable and sustainable for beginners, ultimately enhancing their writing skills and confidence. By understanding the factors that hinder beginners from enjoying and sustaining their writing practice, educators can tailor instructional approaches and interventions that address these challenges. By investigating the benefits and factors affecting enjoy writing by implementing strategies to promote enjoyable writing, educators can effectively contribute to the holistic writing development of beginner.